Collaborative Teaching and Learning through Multi‐Institutional Integrated Group Projects1. (8th July 2013) - Long, Suzanna K.; Carlo, Héctor J.
ABSTRACT This teaching brief describes an innovative multi‐institutional initiative through which integrated student groups from different courses collaborate on a common course project. In this integrated group project, students are asked to design a decentralized manufacturing organization for a company that will manufacture industrial Proton‐Exchange Membrane fuel cells. The groups include students from supply chain management, production planning and scheduling, and facility layout and design courses. Empirical results from the implementation suggest that students responded positively to the integrated experience. Lastly, the article presents implementation strategies for multi‐institutional group projects based on the experiences gained through the collaborative experience.